Outcomes and Complications After Spinal Fusion in Patients With Obstructive Sleep Apnea. Issue 3 (May 2019) - Lin, Charles C.; Lu, Young; Patel, Nilay A.; Kiester, P. Douglas; Rosen, Charles D.; Bhatia, Nitin N.; Lee, Yu-Po
Study Design: Retrospective database study. Objective: To investigate the impact obstructive sleep apnea (OSA) has on perioperative complications, inpatient mortality, and costs in patients undergoing spinal fusions. Methods: Hospitalizations for spinal fusion surgery between the years 2009 and 2011 were identified using the Nationwide Inpatient Sample and grouped into patients with and without OSA. Patient demographic data, comorbidities, hospital characteristics, hospitalization outcomes, and costs were extracted and compared. Multivariable logistic regressions were conducted to compare the in-hospital outcomes of patients undergoing spinal fusion with and without OSA. Results: A total of 107 451 (7.7%) OSA patients who underwent spinal fusions were identified from 2009 to 2011. Compared with patients without OSA, OSA patients were significantly older, more likely to be male, and have significantly greater comorbidity burden. Multivariable regression analysis demonstrated that OSA had a significant independent association with slightly increased respiratory (odds ratio [OR] = 1.13, confidence interval [CI] = 1.09-1.16; P < .001), urinary and renal (OR = 1.11, CI = 1.07-1.16; P < .001) or overall inpatient complications (OR = 1.05, CI = 1.02-1.05; P < .001). OSA was also independently associated with significantly lower inpatient mortality (OR = 0.39, CI = 0.33-0.45; P < .001). Conclusions: While OSA confers greater comorbidity burden and is associated with slightly higher inpatient complication rates following spinal fusions, diagnosed OSA was not an independent predictor of inpatient mortality. A cautious interpretation of this finding is that on a national level, the current methods of preoperative medical optimization and inpatient management of OSA are satisfactory.